(untitled) (Acta Scientiarum. Biological Sciences, 2018)
The ability of microalgae to grow heterotrophically lies in the ability to oxidize organic compounds present in the external environment. The aim of this work was to evaluate the growth of Chlorella vulgaris under heterotrophic culture conditions using Basal Bold and NPK media supplemented with different sole carbon sources (glucose, fructose, sucrose, glycerol or acetate). The kinetic parameters obtained were maximum specific growth rate (µmax), doubling time (DT), maximal absorbance, which was also converted to cell concentration values using a linear relation, and cell productivity (PX). Among all the treatments analyzed, the highest maximum specific growth rate found was 0.030 hour-1 (0.72 day-1) in the treatment using Basal Bold medium supplemented with glucose. The highest cellular concentration and cell productivity were also found for this same treatment (4.03 x 106 cell mL-1 and 64.0 x 106 cell L-1 day-1, respectively). It was concluded that that the Basal Bold medium was more efficient for Chlorella vulgaris growth, since it induced higher values of µmax and cellular concentration. Results obtained were very reproducible using microplate assay.